Epidemiology Aspects of Cutaneous Leishmaniasis in The East Zone of Afghanistan - Rohullah, Asady; Hayatullah, Ahmadzai (Journal for Research in Applied Sciences and Biotechnology, 2024)
Background: Localized cutaneous leishmaniasis (LCL) is a vector-borne disease commonly caused by the flagellate parasites Leishmania tropica or L. major in the Old World. The clinical features of the leishmaniases differ, and in general, these diseases have different geographic distributions. The face, hands, and feet represent the body parts that are most frequently infected by the parasite. If not treat promptly Lieshmania causes permanent scars, in Aghanistan it has become a significant social issue due to limited awareness and the perception that those who suffer from Leishmanian scars are flawed individuals. Methods: This is prospective cross-sectional study conducted from March2023 to February 2024 in Nangarhar University Teaching Hospital including all those patients who had cutaneous Lieshmaniasi. Result: Over the course of a year, this study was carried out in the dermatology department of Nangarhar University Teaching Hospital. 26574 patients visited the Dermatology department this year; 347 (1.3%) of them had cutaneous leishmaniasis, male were more affected by the disease (63.2%); majority of the affected individuals were resident of the rural areas (82.42%) and (84.43%) were represented with ulcerated lesions. five individuals complained about the disease for two years, and one person for four years. Conclusion: Illiteracy, poverty and rural life contribute to the disease’s high incidence in the east zone of Afghanistan. This data can assist health authorities in identifying new focuses, developing an effective strategy for providing health services to the poor in this area